2015
DOI: 10.1242/jeb.116186
|View full text |Cite
|
Sign up to set email alerts
|

Probability distributions of whisker–surface contact: quantifying elements of the rat vibrissotactile natural scene

Abstract: Analysis of natural scene statistics has been a powerful approach for understanding neural coding in the auditory and visual systems. In the field of somatosensation, it has been more challenging to quantify the natural tactile scene, in part because somatosensory signals are so tightly linked to the animal's movements. The present work takes a step towards quantifying the natural tactile scene for the rat vibrissal system by simulating rat whisking motions to systematically investigate the probabilities of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…For the results shown in Figure 6 , an anatomically accurate model of the rat head and vibrissal array was used to simulate vibrissal contact and detach patterns with a vertical wall (Knutsen et al, 2008 ; Towal et al, 2011 ). Whisking kinematics were governed by equations from Knutsen et al ( 2008 ), as in previous work (Hobbs et al, 2015 , in press ). Briefly, the simulated rat was placed in the same position and orientation as the rat in the behavioral video.…”
Section: Methodsmentioning
confidence: 99%
“…For the results shown in Figure 6 , an anatomically accurate model of the rat head and vibrissal array was used to simulate vibrissal contact and detach patterns with a vertical wall (Knutsen et al, 2008 ; Towal et al, 2011 ). Whisking kinematics were governed by equations from Knutsen et al ( 2008 ), as in previous work (Hobbs et al, 2015 , in press ). Briefly, the simulated rat was placed in the same position and orientation as the rat in the behavioral video.…”
Section: Methodsmentioning
confidence: 99%
“…Second, studies on orienting behavior have shown that rats tend to position their heads so as to maximize the number of whiskers in contact with a surface, given the expected orientation of the surface [74,75]. The tendency to maximize the number of whisker-object contacts suggests that the integration of information across multiple whiskers will play an important role during contour extraction.…”
Section: Where Versus What: Determining Object Location and Contourmentioning
confidence: 99%
“…For rodents, the whiskers (vibrissae) are a particularly important sensory modality, and the brain structures associated with the whiskers are correspondingly expanded (Woolsey and van der Loos, 1970;Welker and Woolsey, 1974). Although the rodent whisker system is a premier model for studying active touch (Knutsen et al, 2006;Kleinfeld and Deschênes, 2011;O'Connor et al, 2013;Maravall and Diamond, 2014;Hobbs et al, 2015;Chakrabarti and Schwarz, 2018), we still lack a full understanding of the stimuli that guided the evolution of vibrissaerelated neural structures.…”
Section: Introductionmentioning
confidence: 99%